Diversity of virulence-associated genes in pathogenic Aeromonas hydrophila isolates and their in vivo modulation at varied water temperatures. (October 2020) - Pattanayak, Sabyasachi; Priyadarsini, Swatismita; Paul, Anirban; Kumar, P. Rajesh; Sahoo, P.K.
Abstract: Most environmental parameters have no consistent effect on the expression of bacterial genes responsible for their virulence. However, as fish are poikilothermic, the possibility of temperature variation having a pronounced effect on the expression of virulence-associated gene(s) of bacteria infecting the host needs to be investigated. In this study, the diversity of virulence genes in seven Aeromonas hydrophila isolates collected from diseased fish from different parts of India was characterized, and the effect of temperature variation on the extent of expression of their virulence was investigated. All bacterial isolates were screened for a total of nine bacterial virulent genes {aerolysin, hemolysin, cytoen, outer membrane protein TS (Omp TS), elastase, flagellin, lipase, β hemolysin and type 3 secretion system}, and the diversity in their presence or absence were marked at a particular in vitro condition. Three bacterial isolates (nos. 1, 7 and 2) were selected for further study, based on their ability to cause varied mortalities (20–100%) in Labeo rohita juveniles in intraperitoneal challenge study. Further, three isolates were injected intraperitoneally into L. rohita fingerlings at three different temperatures (i.e., 20, 28 and 37 °C) and at 6 h post-challenge, the kidney samples were collected to measure the levels of all nine bacterial virulence genes using semi-quantitative PCR. The maximum level of amplicons of virulence genes in all three A. hydrophila isolates was noticed at 28 °C as compared to 37 °C and 20 °C. It was also observed that haemolysin played a more prominent role in the expression of virulence, when compared to cytoen gene. Hence, it was concluded that water temperature does play a crucial role in governing virulence gene expression, and a temperature of 28 °C would be considered as suitable for looking into the pathogenicity of A. hydrophila for conducting any challenge study with this organism in tropical environment. Highlights: Studied A. hydrophila virulence related genes in in vitro and in vivo pathogenicity. Investigated pathogenicity of A. hydrophila at varied water temperatures in L. rohita. T3SS identified as a possible marker for identification of pathogenic isolates of A. hydrophila.